Construction of Gendered Identities through Cultural Memory in Moses Isegawa’s Novel, Snakepit - Barasa, Remmy Shiundu (Journal of English Language and Literature (ISSN: 2368-2132), 2017)
Creative writing from Uganda hardly passes without the mention of the Idi Amin era which has significantly influenced the writing from that country. In this paper I examine how Isegawa narrates a people’s cultural memory to define gender identities in his novel, Snakepit. Cultural memory permeates individual as well as social identity formation. Narrating cultural memory results from long interactions with others as well as semiotic objects in a particular social setting. Snakepit was purposively sampled to underscore the interpenetrating relationship between cultural memory and gendered identity formations. The discussion applies itself to the post-colonial theory to explore and make meaning out of the narrative.